ENVIRONMENTAL AUDIT OF THE BANK IN THE CONTEXT OF FINANCING THE GREEN ECONOMY - KUCHER, LESIA; KUCHER, ANATOLII; TRIPILETS, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article, based on the environmental audit of a particular bank, identifies the state, problems and prospects for the development of green banking as a tool for financing the development of the green economy in Ukraine. The method of conducting an environmental audit was formed and tested, which includes the following components: 1) quantitative expert assessment of compliance with the basic principles for responsible banking; 2) qualitative assessment of the bank’s responsible investment practice on the basis of open data; 3) assessment of the readiness of the bank and its staff for green banking. It is established that on average the principles of responsible banking are fulfilled only by 56.5%, which indicates a low level of compliance with these principles. We can conclude that researched bank has no mention of climate change and the Paris Climate Agreement on its website or in its annual reports; it does not participate in international initiatives, funded projects in the green sectors are mainly public-private partnerships and energy efficiency projects under the credit line, data on carbon and environmental footprint are not found in open sources. The bank has not implemented a "green office" system. An empirical study of the readiness of the bank and its staff for green banking was conducted based on a survey of 25 experts. About 64% of the surveyed employees refer the bank to the average level of readiness for green banking. It should be noted that 84% of respondents believe that interested legal entities and individuals would prefer those banks that would have a certified environmental management system. For the development of green banking as a tool of environmental regulation in Ukraine, it is important to have a large player in the market, in which the development of such products and the application of procedures will be identified as a strategic priority. The researched bank may well become such a driver. In this regard, the recommendation is for the management of this bank to set appropriate goals and objectives for the development of green banking to enhance financing of environmental projects, sectors and the application of responsible investment practices.